Potestad sancionadora administrativa por medio del código orgánico monetario y financiero frente a la aplicación del principio pro homine - Ramírez Riofrío, José Antonio (2015)
Fundamental rights are constitutional guarantees for human beings, mandated by law and international treaties, they should be reflected in any legal system in the world. From this precept, we understand that every law of the constitutional norm less than hierarchical level, is required to follow the guidelines provided in the Constitution. Under the document, issued by the supreme law, we have identified a problem in the Code of Monetary and Financial, which on Administrative Law disagrees the Constitution, violating the fundamental rights of individuals under the control of the Superintendency of Popular Economy and Solidarity. What is being tested with this research work is that within the sanctioning administrative power of the inspection body, is impaired people their right to a more favorable interpretation of the rule, which directly affects the principle pro homine, and default the proportionality of administrative penalties. Historically, the Administrative Law has struggled against adversity having no rules according to the reality of the matter, and had to use criminal law as a complementary standard, which becomes a misperception, as being the Law such a dynamic field that evolves over time, due to human behavior and conduct necessary changes in society, it must adapt and specialize to have standards in line with reality and the issues raised. Throughout this thesis, we state the reasons why it believes violates the supreme law, thanks to the doctrinal contribution of several authors skilled in the art and comparative law of Chile and Argentina. Finally, we will base the reform proposal, so that this dissertation is considered, since it will benefit all individuals under the control of the Superintendency.